Does the lower stratosphere provide predictability for month-ahead wind electricity generation in Europe? - Beerli, Remo; Wernli, Heini; id_orcid:0 000-0001-9674-4837; Grams, Christian M. (Quarterly Journal of the Royal Meteorological Society, 2017)
ISSN:0035-9009 ISSN:1477-870X